We have to find the values of constants A and B.
Given the equality in the question, we can write:
![8xe^(6x)=(d)/(dx)[(Ax+B)e^(6x)]](https://img.qammunity.org/2023/formulas/mathematics/college/y8bfkes2c8vs0mps7mom7p6ghkn531hgnc.png)
We then can calculate the derivative as:
![\begin{gathered} (d)/(dx)[(Ax+B)e^(6x)] \\ A\cdot(d)/(dx)(xe^(6x))+B\cdot(d)/(dx)(e^(6x)) \\ A(x\cdot6e^(6x)+e^(6x))+B(6e^(6x)) \\ (6Ax+A+6B)e^(6x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4z3apd4krra141durt8ifod58pzac09a30.png)
Then, we can compare the terms:
![\begin{gathered} (8x)e^(6x)=(6Ax+A+6B)e^(6x) \\ \Rightarrow8=6A \\ \Rightarrow0=A+6B \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kc1n2t63hk6ybglpj8f8hvndff3dxln9wv.png)
We compared the linear and independent terms to find equations to solve for A and B.
Then, we can find A as:
![8=6A\Rightarrow A=(8)/(6)=(4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/rh2we52c3nykx34is064c6bn4axk91hkmd.png)
and B as:
![\begin{gathered} 0=A+6B \\ 6B=-A \\ 6B=-(4)/(3) \\ B=-(4)/(6*3) \\ B=-(4)/(18) \\ B=-(2)/(9) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iyb29fzi969vepm50cwowdxtc91wiqsq9f.png)
Answer: A = 4/3 and B = -2/9.